The Protective Effect of Honey Against Amikacin- induced Nephrotoxicity in Rats - R. Abd Ali, Abeer; H. Ismail, Sajida (Iraqi Journal of Pharmaceutical Sciences, 2017)
Drug –induced nephrotoxicity is an important cause of renal failure. Aminoglycoside antibiotics, such as amikacin, which causes ototoxicity and nephrtotoxicity as a main side effects, this is focused on the use of natural materials as antioxidants against the toxic oxidative action that exert a cell damaging effect. The most important one of these materials is the honey. The aim of this work is to evaluate the antioxidant effects of honey against amikacin – induced nephrotoxicity.18 albino rats divided into 3 groups (6 rats per each group), group 1 received I.P daily dose of normal saline (control), group 2 received (35 mg/kg/day) I.P dose of amikacin ,and group 3 received (35mg/kg/day) of amikacin I.P dose in combination with oral dose of honey(500mg/kg/day) for 2 weeks. All animals (at 15th day) were anesthetized by ether and sacrificed; blood samples were collected for the subsequent measurement of the serum creatinine, urea, malneldehyde (MDA) and glutathione (GSH) while an isolated kidney was kept in 10 % of formaldehyde for the histopathological examination. This study showed that amikacin causes nephrotoxicity represented by elevation of serum level of creatinine and urea, MDA and a decrease in the serum glutathione level. While the administration of honey in combination with amikacin reduced the nephro-toxic effect of amikacin that represented by a reduction of the serum creatinine and urea, MDA and elevation of glutathione levels with improvement of the kidney histological findings in comparison with group 2.This study concluded that, honey decreased nephrotoxicity induced by amikacin through interference with the oxidative stress process, i.e. honey acts as free radical scavenger.Key words:amikacin, honey, nephrotoxicity, oxidative stress.